Design Application of Active Sea Service Based on The Web at KSOP Tanjung Emas - Taufikurrahman, Moh. Rafli; Rohmah, Nur; Iskandar (Dinamika Bahari, 2024)
The process of processing the Active Sea Service Certificate at the Harbormaster and Port Authority (KSOP) of Tanjung Emas is still done manually, making it vulnerable to illegal levies and reliant on paper documents. Therefore, an application is needed to expedite services, enhance efficiency, and minimize the occurrence of illegal levies. This research aims to elucidate the steps for designing a SIMALA application at KSOP Tanjung Emas and to assess its effectiveness. This research employs the Research and Development method, incorporating Planning, Production, and Evaluation (PPE) steps. The effectiveness of the SIMALA application at KSOP Tanjung Emas is gauged using the N-gain value. The process of creating a SIMALA application design at KSOP Tanjung Emas begins with planning, which encompasses preparing tools and materials, conceptualizing the SIMALA application system model, designing the database, structuring database tables, and interface design. The subsequent step is production, involving program and interface implementation. The final step is evaluation, which includes black box testing, phase I improvements, phase II testing, and phase II improvements. The effectiveness of the SIMALA application at KSOP Tanjung Emas falls within the high category, as evidenced by the N-gain value of 0.764.